Whole-Genome Identification and Comparative Expression Analysis of Anthocyanin Biosynthetic Genes in Brassica napus - Dan He; Dan He; Dawei Zhang; Dawei Zhang; Ting Li; Ting Li; Lili Liu; Lili Liu; Dinggang Zhou; Dinggang Zhou; Lei Kang; Jinfeng Wu; et al. (Frontiers in Genetics, 2021)
Anthocyanins contribute to most colors of plants and play protective roles in response to abiotic stresses. Brassica napus is widely cultivated worldwide as both an oilseed and a vegetable. However, only several high anthocyanin-containing cultivars have been reported, and the mechanisms of anthocyanin accumulation have not been well-elucidated in B. napus. Here, the phenotype, comparative whole-genome identification, and gene expression analysis were performed to investigate the dynamic change of the anthocyanin content and the gene expression patterns of anthocyanin biosynthetic genes (ABGs) in B. napus. A total of 152 ABGs were identified in the B. napus reference genome. To screen out the critical genes involved in anthocyanin biosynthesis and accumulation, the RNA-seq of young leaves of two B. napus lines with purple leaves (PL) or green leaves (GL), and their F1 progeny at 41, 91, and 101 days were performed to identify the differentially expressed genes. The comparative expression analysis of these ABGs indicated that the upregulation of TT8 together with its target genes (such as DFR, ANS, UFGT, and TT19) might promote the anthocyanin accumulation in PL at the early developmental stage (41–91 days). While the downregulation of those ABGs and anthocyanin degradation at the late developmental stage (91–101 days) might result in the decrease in anthocyanin accumulation. Our results would enhance the understanding of the regulatory network of anthocyanin dynamic accumulation in B. napus.